2012
DOI: 10.1021/jp305461z
|View full text |Cite
|
Sign up to set email alerts
|

Spin–Orbit Treatment of UV–vis Absorption Spectra and Photophysics of Rhenium(I) Carbonyl–Bipyridine Complexes: MS-CASPT2 and TD-DFT Analysis

Abstract: The lowest-lying spectral transitions in [ReX(CO)(3)(bpy)] (X = Cl, Br, I; bpy = 2,2'-bipyridine) complexes were calculated by means of spin-orbit time-dependent density functional theory (SO-TD-DFT) and spin-orbit multistate complete active space second-order perturbation theory (SO-MS-CASPT2). Computational results are compared with absorption spectra measured in different solvents and used to qualitatively explain the temperature dependence of the phosphorescence decay parameters that were measured for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 48 publications
7
86
1
2
Order By: Relevance
“…18,19,44−46 By combining spectroscopic measurements and CASSCF/MS-CASPT2 and TD-DFT calculations, we have shown that whereas both spinfree and spin−orbit quantum chemical calculations simulate UV−vis electronic spectra of [Re(X)(CO) 3 bpy)] (X = Cl, Br, or I) complexes in a reasonable agreement with experiment, they give a very different interpretation of the absorption bands and only the SO treatment can account for the observed spectral features. 44,46 Going further we computed the spin− orbit coupled TD-DFT potential energy curves as a function of the Re−X bond elongation, as well as of the Re−X bond stretching modes, for the electronic ground state and the lowest excited states of [Re(X)(CO) 3 (bpy)] (X = Cl, Br, or I) taking into account solvent effects. 19,46 When SOC is activated the five lowest electronic excited states, S1, S2, T1, T2, and T3, the electronic densities of which are depicted in Scheme 1 for [Re(Br)(CO) 3 (bpy)], generate 11 "spin−orbit" states of mixed metal-to-ligand-charge-transfer MLCT/halide-LCT character within 0.5 eV, see Scheme 2 and Figure 2 further below.…”
Section: Quantum Chemistry Of [Re(br)(co) 3 Bpy)]mentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,44−46 By combining spectroscopic measurements and CASSCF/MS-CASPT2 and TD-DFT calculations, we have shown that whereas both spinfree and spin−orbit quantum chemical calculations simulate UV−vis electronic spectra of [Re(X)(CO) 3 bpy)] (X = Cl, Br, or I) complexes in a reasonable agreement with experiment, they give a very different interpretation of the absorption bands and only the SO treatment can account for the observed spectral features. 44,46 Going further we computed the spin− orbit coupled TD-DFT potential energy curves as a function of the Re−X bond elongation, as well as of the Re−X bond stretching modes, for the electronic ground state and the lowest excited states of [Re(X)(CO) 3 (bpy)] (X = Cl, Br, or I) taking into account solvent effects. 19,46 When SOC is activated the five lowest electronic excited states, S1, S2, T1, T2, and T3, the electronic densities of which are depicted in Scheme 1 for [Re(Br)(CO) 3 (bpy)], generate 11 "spin−orbit" states of mixed metal-to-ligand-charge-transfer MLCT/halide-LCT character within 0.5 eV, see Scheme 2 and Figure 2 further below.…”
Section: Quantum Chemistry Of [Re(br)(co) 3 Bpy)]mentioning
confidence: 99%
“…44,46 In the Pauli approximation, the electronic Hamiltonian H el is expressed as the sum of the nonrelativistic (electrostatic), H es , and the "spin−orbit", H SO , Hamiltonians:…”
Section: The Model Hamiltonianmentioning
confidence: 99%
“…The identical absorption maxima for 1 and 2, which are only slightly different compared to the Cl precursor 3, and the absence of any >350 nm absorbances in the NAP-free building block 4, confirm the lack of PTZ involvement in the initial excitation event. 89,92,93 Using the transient absorption and infrared spectroscopic data, and extracting energy levels of the electronic states from cyclic voltammetry and emission data, one can construct an energy level diagram for 1 as presented in Fig. Following an initial ultrafast electronic evolution on the 0.5-1 ps timescale, strong stimulated emission is observed at the same spectral position as that assigned to the emission from a [Ph-CuC-Pt-CuC]-to-NAP charge transfer excited state in the steady-state emission spectra.…”
Section: Summary Of the Excited State Processesmentioning
confidence: 99%
“…A number of studies have used quantum wavepacket dynamics, where inclusion of SOC is straightforward; however, these studies are usually restricted to few degrees of freedom. Examples include dihalogens in argon matrices, [80][81][82] transition-metal complexes, [83][84][85][86][87][88][89][90][91][92][93][94][95] and collision reactions. [96] Further, quantum dynamical studies investigated ISC in benzene, [97] hydrogen fluoride, [98] and sulphur dioxide.…”
Section: Introductionmentioning
confidence: 99%